Oral Leukoplakia: Diagnosis And Management Revisited - van der Waal, Isaäc (Journal of Dentistry Indonesia, 2023)
The definition of oral leukoplakia has not much changed during the past five decades and is still a definition by exclusion of ‘known’ lesions. Therefore, a diagnosis of leukoplakia is not always a straightforward one for the clinicians and, to some extent, also for the pathologists. The traditional clinical classification in homogeneous and nonhomogeneous leukoplakia may just be simplified into leukoplakia (thin and thick/verrucous) and erythroleukoplakia. In spite of numerous reported predictive molecular and genetic parameters of malignant transformation, the presence and grade of epithelial dysplasia as assessed by histopathological examination is still the most important one. Of the various treatment modalities, surgery and CO2 laser evaporation are still the most common ones. Treatment may delay or prevent recurrence, but does not seem to prevent malignant transformation or the occurrence of cancer development elsewhere in the mouth or the head and neck region or beyond. There is a strong need for randomized prospective studies and uniform reporting of treatment results..